2018
DOI: 10.7554/elife.34081
|View full text |Cite
|
Sign up to set email alerts
|

Tri-methylation of histone H3 lysine 4 facilitates gene expression in ageing cells

Abstract: Transcription of protein coding genes is accompanied by recruitment of COMPASS to promoter-proximal chromatin, which methylates histone H3 lysine 4 (H3K4) to form H3K4me1, H3K4me2 and H3K4me3. Here, we determine the importance of COMPASS in maintaining gene expression across lifespan in budding yeast. We find that COMPASS mutations reduce replicative lifespan and cause expression defects in almost 500 genes. Although H3K4 methylation is reported to act primarily in gene repression, particularly in yeast, repre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 91 publications
8
80
0
Order By: Relevance
“…S. cerevisiae has a single COMPASS complex containing the catalytic SET‐domain protein Set1 and core structural proteins Swd1, Swd3, Sdc1, Bre2, Swd2, and Spp1. Consistent with the previous report, Cruz et al found that catalytic‐inactive set1 H1017L , Δ swd1, and Δ spp1 mutant yeast strains exhibit significant RLS defect resulting specifically from loss of H3K4me3 (Cruz et al, ).…”
Section: Methionine Metabolism and Lifespan Extension In Yeastsupporting
confidence: 86%
“…S. cerevisiae has a single COMPASS complex containing the catalytic SET‐domain protein Set1 and core structural proteins Swd1, Swd3, Sdc1, Bre2, Swd2, and Spp1. Consistent with the previous report, Cruz et al found that catalytic‐inactive set1 H1017L , Δ swd1, and Δ spp1 mutant yeast strains exhibit significant RLS defect resulting specifically from loss of H3K4me3 (Cruz et al, ).…”
Section: Methionine Metabolism and Lifespan Extension In Yeastsupporting
confidence: 86%
“…Although the precise biological role of H3K4me3 is unclear, its importance is nevertheless apparent. In S. cerevisiae, loss of Spp1 (and therefore H3K4me3) is linked to poor chronological ageing (Cruz et al, 2018;Walter et al, 2014), while murine Cfp1−/− embryonic stem cells are incapable of differentiating (Carlone and Skalnik, 2001). In humans, chromosomal translocations in SET-containing genes are frequently associated with acute myeloid and lymphoid leukemias (Shilatifard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated for 30 min on a wheel at room temperature, washed once with 100 µl PBS and re-suspended in 100 μl PBS, then inoculated in required media at 2x10 4 cells/ml and allowed to recover for 2 hours at 30° before addition of 1µM β-estradiol (Sigma E2758) and CuSO4 as required. For ageing in YPD or YPGal, the same protocol was followed but no recovery period was included -as previously noted this prevents culture saturation without detectable contamination of young cells by 24-48 hours [31]. Cells were harvested by repeated centrifugation for 1 min, 4600 rpm in 50 ml tubes and immediately fixed by resuspension in 70% ethanol and stored at -80°C.…”
Section: Mep Cell Labelling and Purificationmentioning
confidence: 99%
“…Retention of ERCs in mother cells involves tethering by SAGA and TREX2 to nuclear pore complexes, which are themselves largely retained in mother cells, with mutation of SAGA components abrogating retention and extending mother cell lifespan [28][29][30]. ERCs replicate on each division and mother cell retention leads to exponential copy number amplification, increasing genome size by 50% in 24 hours [31], which is thought to interfere with various critical pathways to accelerate, if not cause, ageing pathology [32,33].…”
Section: Introductionmentioning
confidence: 99%